Regional Differences in the Efficiency of German Savings Banks - Peter Reichling; Gordon Schulze (Credit and Capital Markets – Kredit und Kapital, 2018)
German savings banks play a key role in financing German SMEs. Accordingly, the analysis of their efficiency is of economic importance. We apply data envelopment analysis to explore the influence of the financial crisis (2007 to 2008) as well as the Eurozone crisis (since the end of 2009) on the efficiency of German savings banks. Although the Malmquist index, as a measure of efficiency change and technological change, is on average below one in our sample from 2003 to 2014, we conclude from our efficiency results that German savings banks recovered quickly after the financial crisis as well as the Eurozone crisis. We test for and explain regional efficiency differences between Eastern and Western German savings banks. Since Eastern and Western Germany represent two socio-economically different environments, we control for environmental variables. Our results show that Eastern German savings banks are less inefficient than Western German savings banks since other earning assets, i. e., securities and advances to banks, and refinancing costs are advantageous for their efficiency. – – Regionale Unterschiede bei der Effizienz deutscher Sparkassen Deutsche Sparkassen spielen eine wichtige Rolle bei der Finanzierung deutscher KMUs. Die Analyse ihrer Effizienz ist daher von besonderer ökonomischer Bedeutung. Wir verwenden die Data-Envelopment-Analyse, um den Einfluss der Finanzkrise (2007 bis 2008) und der Eurokrise (seit Ende 2009) auf die Effizienz von deutschen Sparkassen zu untersuchen. Obwohl sich der Malmquist Index als ein Maß für Effizienz- und technologische Änderungen in unseren Daten von 2003 bis 2014 im Durchschnitt unter eins bewegt, schlussfolgern wir aus unserer Effizienzanalyse, dass sich die deutschen Sparkassen sowohl nach der Finanz- als auch im Verlauf der Eurokrise schnell erholen konnten. Wir testen und erklären regionale Effizienzunterschiede zwischen ostdeutschen und westdeutschen Sparkassen. Da es sich bei Ost- und Westdeutschland um zwei sozioökonomisch verschiedene Gebiete handelt, berücksichtigen wir Umweltvariablen. Unsere Resultate zeigen, dass ostdeutsche Sparkassen weniger ineffizient sind als ihre westdeutschen Pendants, da sich Vermögensgegenstände in Form von Wertpapieren und Forderungen gegenüber Kreditinstituten sowie die Refinanzierungskosten vorteilhaft auf ihre Effizienz auswirken.
Keywords: C33; C61; G21; 330; Data envelopment analysis; environmental variables; German banking system; Malmquist index